1991
DOI: 10.1149/1.2085535
|View full text |Cite
|
Sign up to set email alerts
|

LPCVD Titanium Nitride for ULSIs

Abstract: Characteristics of TiN films formed by low-pressure chemical vapor deposition (LPCVD) are investigated for application to the barrier layers in ultra-large-scale integration (ULSI) which have fine, high-aspect-ratio contact holes. The evaluation focuses on the characteristics crucial for barrier layer usage, such as step coverage, N/Ti atomic concentration ratio, x, in TiNs, and C1 content. Film resistivities are also measured. Excellent step coverage is confirmed. A high-aspect-ratio hole, such as one with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

1991
1991
2008
2008

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(40 citation statements)
references
References 11 publications
1
39
0
Order By: Relevance
“…4 -9 The high-temperature process which uses TiCl 4 /NH 3 chemistry suffers from particle contamination problems and from Cl incorporation in the film, which is of major concern for long-term device reliability. 4,5 Metalorganic CVD has been used to lower the deposition temperature which also providing conformal films. [6][7][8][9] A recent investigation involving interdiffusion in Cu/CVD TiN thin film structures found that the CVD TiN remained stable up to 450°C for 30 min, after which Cu started to diffuse into the TiN layer.…”
Section: Metalorganic Chemical Vapor Deposition Of Tantalum Nitride Bmentioning
confidence: 99%
“…4 -9 The high-temperature process which uses TiCl 4 /NH 3 chemistry suffers from particle contamination problems and from Cl incorporation in the film, which is of major concern for long-term device reliability. 4,5 Metalorganic CVD has been used to lower the deposition temperature which also providing conformal films. [6][7][8][9] A recent investigation involving interdiffusion in Cu/CVD TiN thin film structures found that the CVD TiN remained stable up to 450°C for 30 min, after which Cu started to diffuse into the TiN layer.…”
Section: Metalorganic Chemical Vapor Deposition Of Tantalum Nitride Bmentioning
confidence: 99%
“…The minimum TiN resistivity of 220 mV Á cm with pure Ti[N(Et) 2 ] 4 precursor was achieved at 500 8C. The lowest observed CVD-produced TiN resistivity value is around 85 mV Á cm, as found by Ramanuja et al [8] and by Yokoyama et al [9] using TiCl 4 precursors at 700 8C, but it is still approximately a factor of 2 higher than the value of 39 mV Á cm reported for the physical vapor deposition (PVD) of TiN films. [10] In order to understand the difference between the minimum resistance values at various temperatures of our TiN layers, obtained from various precursor concentrations, X-ray diffraction (XRD), X-ray reflectivity (XRR), and X-ray photoelectron spectroscopy (XPS) measurements were performed.…”
Section: Resultsmentioning
confidence: 54%
“…TiN may be the most popular among those barrier materials because it has been widely used as a diffusion barrier at the metal/St contact of integrated circuits. TiN can be deposited by either CVD [3] or sputtering [4]. Many materials are under investigation as a source precursor for CD-TiN.…”
Section: Introduction 2 Experimentalmentioning
confidence: 99%